Autophagy-inhibiting polymer as an effective nonviral cancer gene therapy vector with inherent apoptosis-sensitizing ability. (October 2020) - Wang, Jiafeng; Zhou, Xuefei; Wang, Huifang; Xiao, Qian; Ding, Kefeng; Dong, Xue; Xu, Shufeng; Shen, Bo; Sun, Jihong; Zhou, Zhuxian; Tang, Jianbin; Liu, Xiangrui; et al.
Abstract: Conventionally, polycations are pharmacological inert used as nonviral gene delivery vectors with the sole function of compacting and protecting nucleic acids. Here, the first autophagy-inhibiting cationic polymer delivering plasmid DNA (pDNA) encoding TRAIL (tumor necrosis factor-related apoptosis-inducing ligand) is prepared for cancer gene therapy. The copolymerization of methacryloyl chloroquine (MACQ) with 2-(dimethylamino)ethyl methacrylate (DMAEMA) not only improves transfection efficacy through hydrophobic modification, but also endows the copolymer with autophagy-blocking capability, which further sensitizes cancer cells to TRAIL induced apoptosis. Importantly, the designed copolymer shows efficient TRAIL expression, autophagy inhibition and enhances TRAIL-induced apoptosis in an autophagy-dependent manner. In contrast, TRAIL gene delivered by the autophagy-blocking-deficient control copolymer without the chlorine atom presents weaker antitumor efficacy, although expressing a similar amount of therapeutic TRAIL protein. Thus, this study demonstrates a conceptually new approach in which the therapeutic outcome of the delivered gene can be inherently strengthened by the delivery vehicle with intrinsic pharmacological activity.